The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s12978-021-01079-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of sexual and reproductive health knowledge and awareness among single unmarried women living in Lebanon: a cross-sectional study

Abstract: Background Sexual and reproductive health (SRH), a globally recognized fundamental health concern and a basic human right is poorly addressed and seldom researched in the Arab world. Disregarding this aspect of health creates various obstacles to accessing SRH related services and education. This threatens the health of a female, namely through increasing the probability of unplanned pregnancies and unsafe abortions, augmenting the risk of acquiring sexually transmitted infections, and most imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 44 publications
2
10
0
Order By: Relevance
“…The impact of poor knowledge of reproductive health can be reflected by the high percentage (>85%) of participants who reported different types of menstrual disorders. The results are similar to previous reports from developing countries including, Hamadanieh and colleagues who conducted a cross-sectional study to assess the sexual and reproductive knowledge of women in Lebanon [ 16 ]. They reported that less than 10% of the participants to have adequate reproductive health knowledge.…”
Section: Discussionsupporting
confidence: 90%
“…The impact of poor knowledge of reproductive health can be reflected by the high percentage (>85%) of participants who reported different types of menstrual disorders. The results are similar to previous reports from developing countries including, Hamadanieh and colleagues who conducted a cross-sectional study to assess the sexual and reproductive knowledge of women in Lebanon [ 16 ]. They reported that less than 10% of the participants to have adequate reproductive health knowledge.…”
Section: Discussionsupporting
confidence: 90%
“…17 This may be explained by the fact that married women may attend more meetings with gynecologists and be more likely involved in conversations about reproductive issues than unmarried women. However, those visits did not boost unmarried females' sexual and reproductive health knowledge, according to a study conducted by Hamdaniah et al 24 In addition, women with higher educational levels had a greater degree of knowledge, similar to what was observed in other studies. 17,25 This is the first research study to estimate Lebanese women's knowledge and perception toward PCOS that enrolled subjects representative of the general population.…”
Section: Discussionsupporting
confidence: 69%
“…As observed, women incorporated in this study reported considerably varying degrees of knowledge of PCOS. Twenty percent had inadequate knowledge (0-9), 36.4% had satisfactory knowledge (10)(11)(12)(13)(14)(15)(16)(17), and 43.6% had good knowledge (18)(19)(20)(21)(22)(23)(24). The mean knowledge score was determined to be 15.44 AE 7.26 and was graded as satisfactory.…”
Section: Discussionmentioning
confidence: 99%
“…Although pharmacies and shops are a valuable source of short-acting contraceptives, they offer no provision of family planning counseling and knowledge on women's sexual and reproductive health, which are as important as the provision of contraceptives itself. Poor sexual and reproductive health education is associated with higher risks of sexual coercion, unintended pregnancies, induced abortions, and sexually transmitted infections ( 48 , 49 ). In this sense, it is fundamental to consider the potential impact of the high use of these commercial sources by women at the beginning of their sexual and reproductive life.…”
Section: Discussionmentioning
confidence: 99%